2015
DOI: 10.1155/2015/740162
|View full text |Cite
|
Sign up to set email alerts
|

Carqueja (Baccharis trimera) Protects against Oxidative Stress andβ-Amyloid-Induced Toxicity inCaenorhabditis elegans

Abstract: Carqueja (Baccharis trimera) is a native plant found throughout South America. Several studies have shown that Carqueja has antioxidant activity in vitro, as well as anti-inflammatory, antidiabetic, analgesic, antihepatotoxic, and antimutagenic properties. However, studies regarding its antioxidant potential in vivo are limited. In this study, we used Caenorhabditis elegans as a model to examine the antioxidant effects of a Carqueja hydroalcoholic extract (CHE) on stress resistance and lifespan and to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 68 publications
1
17
0
1
Order By: Relevance
“…Some authors have also explored the possible implication of JNK-1 in the polyphenols’ effects, as this transcription factor may also activate DAF-16 in parallel with the IIS pathway [ 124 ]. Studies with the jnk-1(gk7) mutant showed that the life prolonging effects of catechin [ 122 ] and quercetin [ 24 ], or the improvement in the resistance against oxidative stress of extracts from Açai ( Euterpe oleracea ) [ 142 ] or carqueja ( Baccharis trimera ) [ 143 ] were independent of JNK-1.…”
Section: Methodological Approaches For Antioxidants Evaluation In mentioning
confidence: 99%
“…Some authors have also explored the possible implication of JNK-1 in the polyphenols’ effects, as this transcription factor may also activate DAF-16 in parallel with the IIS pathway [ 124 ]. Studies with the jnk-1(gk7) mutant showed that the life prolonging effects of catechin [ 122 ] and quercetin [ 24 ], or the improvement in the resistance against oxidative stress of extracts from Açai ( Euterpe oleracea ) [ 142 ] or carqueja ( Baccharis trimera ) [ 143 ] were independent of JNK-1.…”
Section: Methodological Approaches For Antioxidants Evaluation In mentioning
confidence: 99%
“…RNA interference (RNAi) was performed using the feeding method described previously, with empty pL4440 as controls [ 27 ]. Briefly, RNAi clones were grown with 12.5 μ g/mL tetracycline and 100 μ g/mL ampicillin.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the lifespan extension produced by quercetin-3-O-diglucoside in C. elegans was explained by upregulation of the genes daf-2, old-1, osr-1, and sek-1, whereas no modification was produced in the expression of daf-16, age-1, and sir-2.1 [12]. However, assays with a flavonol-rich extract obtained from Baccharis trimera concluded that the improvement in the stress resistance was independent of several stress-related signaling pathways (p38, JNK, and ERK) and transcription factors SKN-1 and DAF-16 [32].…”
Section: Q-rt-pcr Analysesmentioning
confidence: 99%